Changes in Implementation of the "Balahak" Tradition of the Bride Based on Education in the Siulak Community, Kerinci Regency - Jambi - Sofrina Zulida Fatma; Agustina Agustina; Agusti Efi (International Journal of Educational Dynamics, 2021)
This study aims to describe the changes in the implementation of the bridal Balahak tradition in the Siulak community in Kerinci Regency, and to describe the causes of changes in the implementation of the bridal Balahak tradition in the Siulak community in Kerinci Regency. This study used a descriptive qualitative method by describing or describing the circumstances that occurred in the object under study, in this case, the change in the implementation of the bridal Balahak tradition in the Siulak community in Kerinci Regency. The results of this study were obtained by data collection techniques in the form of observation, interviews, literature study, and documentation. This study found that several changes occurred in the bridal Balahak tradition in the Siulak community, the factors causing the change in the Balahak tradition were the times, economy, lineage or cultural contact, and the open nature of society.